Analisis Cost Benefit Pemupukan Berimbang Dalam Rangka Pemenuhan Unsur Hara Optimal: Pendekatan RIA: Institut Pertanian Bogor - Widyastutik; Muhammad Firdaus; Mimin Aminah; Dian Verawati Panjaitan (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2022)
The government prepares recommendations for optimal fertilization according to plant needs, optimum for increasing production, increasing fertilization efficiency, soil fertility, and avoiding environmental pollution. However, the condition of agricultural land in Indonesia shows an excess of P and K nutrients from NPK 15-15-15. As a result, the soil becomes saturated, wasteful, and import costs are high in the long term. For this reason, the government reformulated from NPK 15-15-15 to 15 10 12. So the purpose of this research is to find out the benefits and costs of changing this formulation using the RIA (Regulatory Impact Assessment) method with three scenarios. Based on calculating the benefits and costs of the NPK fertilizer formulation that provides the most benefits, scenario 3 uses the NPK 15 10 12 formula with straw immersion innovation and soil and plant test equipment. The total benefit obtained is Rp. 323,988,364.65. Straw as a source of Potassium (K), Silica (Si), and microelements and a source of energy for soil microorganisms are recommended to be returned to paddy fields to increase fertilization efficiency soil fertility, improve, and maintain soil health and environmental quality. The effectiveness of the reformulation policy of NPK 15 15 15 to NPK 15 10 12 needs to be supported by advocacy to farmers regarding the benefits that will be obtained when implementing balanced fertilizers to get optimal crop yields. Lessons from farmers who successfully buried straw that impact rice production and productivity must be disseminated to other farmers.